Thermophysical Properties of Molten Stainless Steel Containing 5 mass % B4C. (2nd September 2019) - Fukuyama, Hiroyuki; Higashi, Hideo; Yamano, Hidemasa
Abstract: An electromagnetic levitation technique performed in a static magnetic field was used to measure density, surface tension, normal spectral emissivity, heat capacity, and thermal conductivity of molten 316L stainless steel (SS316L) and SS316L that contained 5 mass % B4 C. The addition of 5 mass % B4 C to the SS316L yielded reductions of 111 K, 6%, 19%, and 6% in the liquidus temperature, density, normal spectral emissivity, and thermal conductivity at the liquidus temperature of the SS316L, respectively. The heat capacity increased by 5% with this addition. Although the addition of 5 mass % B4 C had no clear effect on the surface tensin, sulfur dissolved in the SS316L caused a significant decrease in the surface tension.